Body mass index (BMI) and alpha-fetoprotein (AFP) level correlate with the severity of HCV-induced fibrosis in a cohort of Egyptian patients with chronic HCV - Amal Ahmed Mohamed; Amr Ali Hemeda; Ramy Karam Aziz; Mohamed Salaheldin Abdel-Hakeem; Marwa Ali-Tammam (SpringerOpen, 2020)
Abstract Background Viral hepatitis is the seventh leading cause of mortality globally, and half of this mortality is attributed to hepatitis C virus (HCV). Egypt has the highest HCV prevalence worldwide, with an estimated 14.7% of the population being HCV-positive. HCV infection is the primary cause of liver fibrosis, cirrhosis, and hepatocellular carcinoma. Liver fibrosis varies in severity during chronic HCV infection, and 10-20% of chronic hepatitis C (CHC) patients with severe fibrosis develop cirrhosis. The goal of this work was to assess the clinico-demographic predictors of severity of HCV-induced fibrosis in a cohort of Egyptian patients. Results A cohort of Egyptian patients with chronic HCV genotype 4a infection showed significant association between severe fibrosis stages and obesity, represented by a higher body mass index (BMI), low albumin level, high alpha-fetoprotein (AFP) level, low thyroid-stimulating hormone (TSH) level, and high alkaline phosphatase (ALP) level. Multivariate analysis delineated BMI, TSH, and ALP as independent significant variables that could predict the risk of fibrosis severity in HCV infections. Conclusion This study argues in favor of using the biomarker profile of CHC patients infected with HCV genotype 4a to identify patients at higher risk of developing severe fibrosis, which is a necessary first step towards precision medicine via patient stratification.